Metrics for Quantification of By-Process Segregation in Ge-Rich GST - Petroni, Elisa; Serafini, Andrea; Codegoni, Davide; Targa, Paolo; Mariani, Luca; Scuderi, Mario; Nicotra, Giuseppe; Redaelli, Andrea (Frontiers in Physics, 2022)
Ge-rich GST alloys are the most promising materials for phase-change memory (PCM) to fulfill the soldering compliance and the tough data retention requirements of automotive applications. Big efforts have been thus put to engineer those materials and optimize their integration inside the fabrication process of PCM. In this perspective, the physical characterization of the device and the material is instrumental to understand the underlying physics, to improve the process and optimize the interactions between the device, the process, and the material itself. Especially, microscopic investigations have gathered increasing interest, giving detailed descriptions of local material modulations that have a crucial role for cell programming and reliability performances. In this work, a deep analysis of Ge-rich GST microscopic alloy evolution during integration process has been performed, exploiting chemical analysis at Transmission Electronic Microscope supported by a novel statistical data post-processing method. The new proposed statistical-based methodology also introduces new simple metrics for elemental compositional evaluations that have been exploited for process engineering.